The influence of managerial myopia on firm strategy. Issue 3 (13th May 2014) - W. Ridge, Jason; Kern, Dave; A. White, Margaret
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to examine the effects of temporal myopia (focussing on the short-term) and spatial myopia (focussing on the current market) on firm strategy. Specifically the paper investigates the effects of temporal and spatial myopia on the persistence and conformity of firm strategy. Additionally, the paper tests how environmental munificence moderates these effects. A secondary purpose of this paper is to develop a replicable method of measurement of temporal and spatial myopia. Design/methodology/approach – The authors conducted a manual content analysis of letters to shareholders for 100 firms over three years to measure spatial and temporal myopia. After collecting strategy variables and control variables from Compustat, the authors utilize a random-effects panel methodology. Findings – The results indicate that strategy is influenced by both temporal and spatial myopia. Specifically, temporal myopia creates a focus on the firm's current strategy, leading to a persistent strategy over time and spatial myopia focusses firm decision makers on better known technologies and competitors, leading to conformity to industry strategic profiles. Additionally, the paper tests how environmental munificence influences these relationships. In total, the paper finds that the differing types of managerial myopia have distinct influences on firm outcomes. Originality/value – This paper makes two important contributions to the literature on managerial myopia. First, the paper investigates the differential effects of both spatial and temporal myopia on firm strategy, topics that have been relatively overlooked in empirical investigations of decision making. Second, the paper develops replicable measures for both temporal and spatial myopia, which have been previously suggested to limit the ability to empirically test the implications of managerial myopia (Laverty, 1996).